Research on the Fine Control of the Influence of Pipe-Jacking Parameter Deviation on Surrounding Stratum Deformation - Tianlong Zhang; Guoqing Chen; Ping Lu; Dongqing Nie (Applied Sciences)
Based on the Zhuyuan–Bailonggang sewage interconnection pipe project in Shanghai, the ABAQUS finite element software was used in numerical simulations to study the fine control of stratum disturbances caused by pipe jacking parameter deviation in soft soil areas. Combining the simulation results with onsite measured data, the Peck formula was used to predict surface settlement. The results indicate the following: (1) The jacking speed and face pressure are negatively correlated with surface settlement. Under the maximum positive deviation and negative deviations in the jacking speed, after the tail passes through the monitoring section D0 16 ring, the maximum value of settlement at point B8 increases by 21.6% and decreases by 12.8%, respectively. Increasing the jacking speed increases the area with stress change ratio R < 0 at monitoring section D0, and the arch foot at the tail of the pipe jacking machine decreases the surface settlement. In contrast, when the face pressure deviates from its average value, the variation range is less than 1%. (2) The pipe slurry coefficient and surface subsidence are positively correlated. Under the maximum positive deviation and the maximum negative deviation, the tail passes through the monitoring section D0 16 ring, and the maximum settlement value at B8 decreases by 4.9% and increases by 16.5%, respectively. The increase in the coefficient reduces the area with R < 0 at D0 and increases the surface settlement. (3) In the order of descending strength, surface settlement is affected by the jacking speed, slurry friction coefficient, and face pressure. (4) To predict the maximum surface settlement value due to deviations in the jacking parameters, the Peck formula was modified using a correction factor <semantics>α</semantics> ranging from 0.6 to 3.0 and a settlement trough width correction factor <semantics>β</semantics> ranging from 1.6 to 4.0. The modified prediction curve is in closer agreement with the actual conditions.